Relasi Perdamaian dan Pembangunan dalam Krisis Rohingya - Aditya Hasymi (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2019)
Abstract The strength of a nation is strongly influenced by economic capacity. History prove that conflicts and wars occurs cause of the race for economic source of wealth. The emergence of economics as source of conflict has become an important discourse in peace studies. No exception to what happened in Rohingya, Myanmar. A case of civil conflict in Myanmar has surfaced internationally due to the turnaround from abuse of human rights issue to development conflict. This study wants to assess relations between the concept of peace and economic development in Rohingya crisis. The following question is central to this research: why mutual connection between peace process and economic development process emerge in case of Rohingya crisis? In approaching the main research question, this paper employs an analytical framework with core argument linked to the literature on capitalist peace theory. This paper will use qualitative method and library research to analyse factors of mutual connection between peace and economic development in Rohingya crisis. Through tracing process from several literatures, it is revealed the factors of mutual connection between peace and economic development in Rohingya crisis: first, economic motives in land grabbing by the military disturbed the stability of peace in Myanmar, and second, there is iniquity in development of rural communities in Myanmar by expelled the minority Rohingya. Keywords: Peace; development approach; Rohingya crisis; land grabbing Abstrak Kekuatan dari sebuah negara amat terpengaruh dari kekuatan ekonominya. Sejarah membuktikan bahwa konflik dan perang terjadi dikarenakan persingan memperebutkan sumber kesejahteraan ekonomi. Kumunculan dari ekonomi sebagai sumber konflik telah menjadi hal penting dalam studi perdamaian. Tak terkecuali dengan apa yang terjadi di Rohingya, Myanmar. Sebuah kasus konflik sipil di Myanmar yang menjadi kasus internasional karena adanya pergeseran isu dari etnis dan agama menjadi isu hak asasi manusia karena adanya pengambil alihan lahan secara paksa. Penelitian ini menganalisa bagaimana relasi antara konsep pendekatan pembangunan sebagai perdamaian dalam konflik Rohingya. Penelitian ini menggunakan kerangka kerja pendekatan pembangunan (development approach) dalam penyelesaian konflik. Penelitian ini akan menggunakan metode penelitian kualitatif dan studi literatur. tiga fokus kerangka kerja yang terdapat dalam pendekatan pembangunan (development approach) yaitu: pembangunan untuk memenuhi kebutuhan dasar dan hak asasi manusia untuk membebaskan manusia dari berbagai bentuk kekerasan, kemiskinan, represi, ketidakamanan, dan alienasi budaya; pembangunan dalam upaya penyelesaian konflik harus dijalankan oleh struktur dan kelembagaan ekonomi dan politik; dan ketiga, strategi dan perencanaan pembangunan sebagai perdamaian harus peka terhadap konflik dan bertumpu pada perdamaian. Kata kunci: perdamaian; pendekatan pembangunan; krisis Rohingya; ambil alih lahan.